2000
DOI: 10.1001/archinte.160.20.3160
|View full text |Cite
|
Sign up to set email alerts
|

Cost for Inpatient Care of Venous Thrombosis

Abstract: There was no significant difference in the overall cost for the 3-month episode of care for patients treated with either enoxaparin or unfractionated heparin. Additional acquisition costs for anticoagulant medication among patients treated with enoxaparin were offset by savings associated with lower incidence of hospital readmission and shorter duration of venous thromboembolism-related readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A number of studies have indicated that the LMWHs are economically superior to UFH both for DVT treatment [80,83,84], and for bridging to long-term anticoagulation [85-87], and they are at least non-inferior or superior to warfarin in preventing VTE following orthopedic surgery [88,89]. However, there are limited data regarding the economics associated with thromboprophylaxis following cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have indicated that the LMWHs are economically superior to UFH both for DVT treatment [80,83,84], and for bridging to long-term anticoagulation [85-87], and they are at least non-inferior or superior to warfarin in preventing VTE following orthopedic surgery [88,89]. However, there are limited data regarding the economics associated with thromboprophylaxis following cancer surgery.…”
Section: Introductionmentioning
confidence: 99%